(3GdJacjQ hGdGYJHGQ aj aVd GdUdGI Ydi GdfHi GdeNJGQs - (3GdHLGFj , CMeO Hf KGHJ GdMSjfj GdHLGFj, CHh GdYHGS,J (B1152 (3g` s ((3eMeO Hf Ydi Hf UGdM s)
(3ChdgG (B:s
(3GdMeO ddg GdPi GdEfSGf HfYaJI hUhQg ai GdCQMGe cja TGA HMceJg s
(3BNQgG (B:s
(3hJHdi UhQI JMJ GdJQGH Je GdcJGH s
(3GdfSNI HgG MhGTs
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B1 - (3U (B180s
(3EjVGM Gdecfhf ddHZOGOi(B: (3L (B1 - (3U (B312s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG JdhjK s
Keywords: (3GdJUha hGdBOGH GdTQYjIs